Rules and regulations of The United Brothers' Birmingham Benefit Society (London : J.S. Forsaith & Son, Printers (T.U.), 1908)
1908 1908 1900s 18 pages 12 21. Should the expenditure of this society at any time exceed the income, the stewards shall be empowered to order an extra amount of contribution to be paid by each member until the income cover the expenditure. 22. Should any dispute at any time arise that these rules do not embrace, the secretary shall call on the committee to inquire into such complaint, should the complaining member not be satisfied with the committee's decision, he shall ask the secretary to summon a general meeting, whose decision shall be final. 23. That this society shall not be dissolved so long as thirteen members hold together, and no rules for the government of the same be made without the consent of the majority of the members present at a general meeting held for that purpose, when all absent members shall conform to the same, or be excluded ; the new rules to be entered in a book, and to be of as good effect as those printed. Any member proposing the dissolution of the society shall be fined five shillings, to be paid with the quarter's arrears, or be excluded. 24. That on the quarterly night in December, any member who neglects to clear the books of all arrears, so that the secretary may make a division of the stock, shall be fined two shillings ; the same with his arrears of contribution, and two shillings and sixpence, to remain as such stock, will be deducted from his share ; and should the share not be sufficient to pay his arrears he shall pay the difference on the next meeting night. Members neglecting to clear the books on the second meeting night after sharing night to be fined sixpence. 25. That there be two auditors appointed on the quarterly night to audit the accounts of the preceding quarter ; they shall appoint a night to attend with the secretary for that purpose, for which they shall receive sixpence each for their services ; any member accepting the office of auditor and not attending to his duty will be fined sixpence; the secretary to call on any member present as a substitute, for which he shall receive sixpence; and on the first meeting night in each year each 345/7/2/2